2013
DOI: 10.1111/jse.12034
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the morphology, anatomy, and ontogeny of Adiantum capillus‐veneris: An experimental system to study the development of ferns

Abstract: Adiantum capillus-veneris L., commonly regarded as a good experimental plant for the study of fern development, is investigated, and its life cycle under laboratory conditions is described. In our study, the life cycle of A. capillus-veneris was completed in 100 days. Features of spore germination, antheridium and archegonium ontogeny and development, and embryogenesis are investigated. Exosporic gametophytes of A. capillus-veneris came from spores, and ended with the cordate prothallia. Antheridia and archego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 44 publications
(58 reference statements)
2
25
0
Order By: Relevance
“…Spores observation under the microscope showed that the first cell observed from both locations were green. This result is consistent with the previous study in Adiantum that showed spore germination of Adiantum capillus-veneris began at the third or fourth day after planting, and rhizoid elongation from new spores occurred in the next two days [15]. The first green cells in gametophyte formation played a role in photosynthesis [16].…”
Section: Spore Germinationsupporting
confidence: 93%
“…Spores observation under the microscope showed that the first cell observed from both locations were green. This result is consistent with the previous study in Adiantum that showed spore germination of Adiantum capillus-veneris began at the third or fourth day after planting, and rhizoid elongation from new spores occurred in the next two days [15]. The first green cells in gametophyte formation played a role in photosynthesis [16].…”
Section: Spore Germinationsupporting
confidence: 93%
“…The opening of false indusia is driven by desiccation (cf. [ 15 , 16 ]). Most presumably, the microclimate inside the cavity formed by the closed false indusium prevents the sporangia from losing water and hence hinders spore ejection before the actual opening of the false indusium.…”
Section: Resultsmentioning
confidence: 99%
“…Concomitant with the development of numerous sporangia on their abaxial surfaces, the false indusia change color from light green to dark brown ( Fig 1B ) and flap open due to evaporative forcing (cf. [ 15 , 16 ]). The movement of the false indusium leads to sporangium exposure and can be considered as the first step in the process of spore release ( Fig 1C ).…”
Section: Introductionmentioning
confidence: 99%
“…For A. capillus-veneris , samples were collected from plants cultivated in the greenhouse of Peking University (Voucher specimen was deposited in PEY). We chose roots, shoots, curled leaves, young leaves, fully developed leaves, immature sporangia, mature sporangia, immature gametophytes, reproductive gametophytes, and embryos as materials (Li et al, 2013). Total RNA of plant materials was isolated with Plant RNA Extraction Reagent (Invitrogen, USA) and purified with an RNeasy Mini kit according to the manufacturer’s instructions (Qiagen, Germany).…”
Section: Methodsmentioning
confidence: 99%